Pengaruh Work freedom, E-Commerce, Risk tolerance, dan Entrepreneurship education terhadap Minat Berwirausaha Mahasiswa FEB Jakarta Barat - Evelin, Catherine; Amelinda, Rita (Sekolah TInggi Ilmu Administrasi dan Manajemen Kepelabuhan (STIAMAK) Barunawati Surabaya, 2025)
Abstract. This study aims to examine the influence of work freedom, e-commerce, risk tolerance, and entrepreneurship education on the entrepreneurial intention of students in the Faculty of Economics and Business at campuses located in West Jakarta. The research method applied is quantitative, using purposive sampling in the sample selection process. Primary data were collected from students of the Faculty of Economics and Business at campuses domiciled in West Jakarta, while secondary data were obtained from books and journals previously studied by other researchers. The findings reveal that the independent variables—work freedom, e-commerce, risk tolerance, and entrepreneurship education—explain or influence the dependent variable, entrepreneurial intention, by 0.945 or 94.5%, while the remaining 5.5% is influenced by other factors outside the study. The results further indicate that work freedom, e-commerce, risk tolerance, and entrepreneurship education have a positive and significant effect on entrepreneurial intention.